Genetic Variation for Wild Populations of the Rare and Endangered Plant Glyptostrobus pensilis Based on Double-Digest Restriction Site-Associated DNA Sequencing - Yongrong Huang; Yu Li; Xiaojie Hong; Suzhen Luo; Dedan Cai; Xiangxi Xiao; Yunpeng Huang; Yushan Zheng (Current Issues in Molecular Biology)
Glyptostrobus pensilis is an endangered tree species, and detecting its genetic diversity can reveal the mechanisms of endangerment, providing references for the conservation of genetic resources. Samples of 137 trees across seven populations within Fujian Province were collected and sequenced using double-digest restriction site-associated DNA (ddRAD-seq). A total of 3,687,189 single-nucleotide polymorphisms (SNPs) were identified, and 15,158 high-quality SNPs were obtained after filtering. The genetic diversity in the populations was found to be low (Ho = 0.08630, He = 0.03475, π = 0.07239), with a high genetic differentiation coefficient (Fst). When K = 4, the coefficient of variation (CV) error value was minimized, suggesting that the 137 individuals could be divided into four groups, with frequent gene flow between them. Principal component analysis (PCA) divided the seven populations into two major categories based on their north–south geographic location. The clustering was consistent with those obtained from the PCA. The main reasons for the endangerment of G. pensilis are likely to be poor natural regeneration, human disturbances, and climatic factors. It is recommended that methods such as in situ conservation, ex situ conservation, and the establishment of germplasm banks be implemented to maintain the genetic diversity of G. pensilis populations.